(untitled) (Kronika Bydgoska, 2012)
Money boxes from the archaeological research in Bydgoszcz are ceramic vessels madę on the potter’s wheel, completely closed, of round shape on a cylindrical base. With a handle knob in the highest point. In the top part of the money box body, there is a narrow, rectangular crack for inserting coins cut out before burning them. The shape of the Bydgoszcz money boxes is typical of this type vessels, still manufactured by traditional potter’s workshops in our times. The nearest similar to the entirely preserved historical artefact comes from Tuchola, where the found money box was dated back generally to the modern period. Another artefact similar to ours comes from Bieździadowo, where it had been used as a vessel for a treasure deposited after the year 1773. Besides functioning as ‘home treasuries’, the money boxes had been used as vessels for coin treasures in the 14th- 18th centuries. Noteworthy is a little diversity of forms of money boxes known from the archaeological research in Poland. Sparse examples of money boxesin the shape of animals are known.